Two boron-containing compounds affect the cellular viability of SH-SY5Y cells in an in vitro amyloid-beta toxicity model - OZANSOY, Mehmet (Turk J Biol, 2020)
Boron is a naturally occurring trace element found in organic and inorganic complexes. Boron-containing compounds are required for living organisms for diverse metabolic functions, including nitrogen fixation in microorganisms, cell wall stability in plants, and bone and carbohydrate metabolism in animals. The number of studies about the effect of boron in biological model systems is very limited; so far, there has been no study on the correlation between boron and amyloid-beta toxicity. Here, we investigated the possible effects of 2 boron-containing compounds—sodium borate decahydrate and boric acid—against amyloid-beta toxicity. In our in vitro amyloid-beta toxicity model, we showed that these 2 compounds increase the survival of the SH-SY5Y cells. Furthermore, boron in these 2 forms increases the expression of Sirt1, which has protective functions against cellular stress. The compounds also change the expressions of GSK-3α/β; by doing so, boron may contribute to the stimulation of intracellular prosurvival pathways. This is the first experimental study indicating the prosurvival effect of boron in an amyloid-beta toxicity model.